1998
DOI: 10.1523/jneurosci.18-22-09335.1998
|View full text |Cite
|
Sign up to set email alerts
|

Persyn, a Member of the Synuclein Family, Has a Distinct Pattern of Expression in the Developing Nervous System

Abstract: The synucleins are a unique family of small intracellular proteins that have recently attracted considerable attention because of their involvement in human neurodegenerative diseases. We have cloned a new member of the synuclein family called persyn. In contrast to other synucleins, which are presynaptic proteins of CNS neurons, persyn is a cytosolic protein that is expressed predominantly in the cell bodies and axons of primary sensory neurons, sympathetic neurons, and motoneurons. Northern blotting, in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(156 citation statements)
references
References 40 publications
2
151
0
3
Order By: Relevance
“…However, we have recently observed that the subcellular localization of ␥-synuclein in tumor cells may be altered. Previous studies have shown that ␥-synuclein is diffusely distributed in the cytoplasm of peripheral neurons, although it is also expressed in the brain (46). We have found in tumor cells, which over-express the wild-type ␥-synuclein, that the protein tends to accumulate in the nuclei.…”
Section: ␥-Synuclein In Cancer Cell Apoptosis and Drug Resistancementioning
confidence: 56%
“…However, we have recently observed that the subcellular localization of ␥-synuclein in tumor cells may be altered. Previous studies have shown that ␥-synuclein is diffusely distributed in the cytoplasm of peripheral neurons, although it is also expressed in the brain (46). We have found in tumor cells, which over-express the wild-type ␥-synuclein, that the protein tends to accumulate in the nuclei.…”
Section: ␥-Synuclein In Cancer Cell Apoptosis and Drug Resistancementioning
confidence: 56%
“…Furthermore, the expression and intracellular localization of ␣-and ␤-syn are very similar in that both proteins are predominantly expressed in neurons of the central nervous system and are concentrated at the presynaptic terminal (19 -22). In contrast, ␥-syn is predominantly expressed in neurons of the peripheral nervous system, although it is also found at low levels in brain but diffusely distributed throughout the cytoplasm (23). Synoretin is similar to ␥-syn with respect to amino acid sequence and intracellular distribution, but synoretin is mainly expressed in the retina (17).…”
mentioning
confidence: 99%
“…tubulin) [55,101] and other amyloidogenic proteins (i.e. tau) [19,102]. Jensen et al [103] have hypothesized that an interaction between α-Syn and tau could link synaptic vesicles with microtubules.…”
Section: Phosphorylation At Serine129 Modulates α-Synuclein Protein-pmentioning
confidence: 99%